2013
DOI: 10.1159/000353376
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Oscillatory Ventilation with Low Oscillatory Frequency in Pulmonary Interstitial Emphysema

Abstract: Background: Pulmonary interstitial emphysema (PIE) is a common respiratory illness in preterm infants associated with significant morbidity and mortality for which the ventilatory management is imperfect. Objectives: To evaluate the impact of high-frequency oscillatory ventilation (HFOV) with a low oscillatory frequency and thus prolonged expiratory time in preterm infants with severe PIE. Methods: In a retrospective cohort study, preterm infants ≤30 weeks' gestation with radiological findings of severe PIE, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
(24 reference statements)
0
22
0
1
Order By: Relevance
“…17,18 The majority of randomized control trials reported using HFOV frequencies between 10 and 15 Hz in premature infants with respiratory failure. 4 Squires et al 19 describe the utilization of lower HFOV frequencies (5-6 Hz) to afford a longer expiratory phase in infants with pulmonary interstitial emphysema and concluded that this strategy may provide some benefit in gas exchange. Reducing HFOV frequency concomitantly increases the inspiratory time, results in larger V T , and could potentially exacerbate lung injury in infants with low lung compliance.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The majority of randomized control trials reported using HFOV frequencies between 10 and 15 Hz in premature infants with respiratory failure. 4 Squires et al 19 describe the utilization of lower HFOV frequencies (5-6 Hz) to afford a longer expiratory phase in infants with pulmonary interstitial emphysema and concluded that this strategy may provide some benefit in gas exchange. Reducing HFOV frequency concomitantly increases the inspiratory time, results in larger V T , and could potentially exacerbate lung injury in infants with low lung compliance.…”
Section: Discussionmentioning
confidence: 99%
“…High-frequency oscillatory ventilation may be beneficial in clinical MAS complicated by pulmonary interstitial emphysema [20]. Zagariya et al [21] used an animal model and compared the effects of saline, milk and meconium instillation into the rabbit lungs.…”
Section: Inflammation In Mas - Lessons Learned From Experimental Studiesmentioning
confidence: 99%
“…For selective intubation to be successful, the tip of the endotracheal tube (ETT) must be passed into the opening of the right main bronchus and kept in that position to facilitate collapse of the left lung. The duration of this procedure depends on how quickly the lung collapses and if the baby can tolerate single lung ventilation.The preferred duration of selective main stem intubation reported in the literature varies arbitrarily from 1 to 10 days . In some cases, the combination of selective intubation and HFOV have been used with an approach of low oscillatory frequency and a reduced mean airway pressure .…”
Section: Discussionmentioning
confidence: 99%
“…The duration of this procedure depends on how quickly the lung collapses and if the baby can tolerate single lung ventilation.The preferred duration of selective main stem intubation reported in the literature varies arbitrarily from 1 to 10 days . In some cases, the combination of selective intubation and HFOV have been used with an approach of low oscillatory frequency and a reduced mean airway pressure . This is important in the management of PIE as this decreases the driving pressure of the gas through the leak site.…”
Section: Discussionmentioning
confidence: 99%